2005
DOI: 10.1096/fj.04-2386com
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel functional androgen response element withinhPar1promoter: implications to prostate cancer progression

Abstract: Human protease-activated receptor-1 (hPar1) plays a role in malignant and physiological invasion processes. We have identified a functional androgen response element (ARE) located in the hPar1 promoter upstream of the transcription start site at -1791 to -1777. Dihydrotestosterone treatment of the prostate cancer cell line LNCaP increased endogenous hPar1 mRNA levels, consistent with the threefold increase in promoter activity of hPar1-luciferase reporter construct. Specific binding of the hPar1-derived ARE to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Among the activators are Sp1 (Tellez et al, 2003), androgen/ hormone response elements (Salah et al, 2005) and Egr-1 (Salah et al, 2007a). The repressors are AP-2 (Tellez et al, 2003) and wt p53 (this study).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Among the activators are Sp1 (Tellez et al, 2003), androgen/ hormone response elements (Salah et al, 2005) and Egr-1 (Salah et al, 2007a). The repressors are AP-2 (Tellez et al, 2003) and wt p53 (this study).…”
Section: Discussionmentioning
confidence: 67%
“…Rather, it is because of increased hPar1 transcription as evaluated by amplified transcription rates in aggressive versus non-aggressive prostate cancer lines. Indeed, we have identified Egr-1 as a critical regulator of hPar1 gene overexpression in the hormoneindependent prostate carcinoma (Salah et al, 2005(Salah et al, , 2007b.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the prostatic expression of PAR 1 , androgen regulation of the encoding gene has been recently reported (Salah et al, 2005). These workers showed that stimulation of LNCaP cells with dihydrotestosterone (DHT) increased the transcription of PAR 1 , whereas PC-3 cells, which lack an androgen receptor, were unresponsive.…”
Section: Par Expression In Prostate Tissue and Cell Linesmentioning
confidence: 60%
“…However, as PAR 1 levels are elevated in late, androgen independent stage disease it is apparent that other mechanisms must also transcriptionally regulate the encoding gene. Consistent with this proposal, an aggressive, hormone resistant sub-line of LNCaP cells (CL1 cells) generated through in vitro androgen deprivation, has high levels of PAR 1 mRNA and protein and small amounts of AR protein; a phenomenon that is also seen in PC-3 cell which lack androgen receptor (Salah et al, 2005). More recently, Salah and colleagues employed fluorescence in situ chromosome hybridisation to indicate that differences in PAR 1 mRNA levels in cell lines of high (CL1 or PC-3) and low (LNCaP) expression is not due to gene amplification.…”
Section: Par Expression In Prostate Tissue and Cell Linesmentioning
confidence: 65%
“…In addition to the well-established role of PAR 1 in thrombosis, hemostasis, and vascular biology, its role in tumor biology is currently emerging (1)(2)(3). We, as well as several independent laboratories, have highlighted the central involvement of PAR 1 in epithelial malignancies (4)(5)(6)(7)(8)(9). In fact, PAR 1 serves as a delicate cell sensor to mediate the function of classical enzyme/s centrally involved in thrombosis and hemostasis.…”
Section: Introductionmentioning
confidence: 99%